Strategi Pengembangan Model Bisnis E-Commerce Batik Suku Baduy Berbasis WordPress dengan Analisis Business Model Canvas dan Fishbone Diagram - Windhy Widhyanti; Retno Wulandari (CV. Multi Kreasi Media, 2025)
study aims to design and analyze a WordPress-based e-commerce website as a marketing platform for Batik products of the Baduy ethnic community. The main challenges faced by Baduy batik entrepreneurs are limited market access and the lack of optimal utilization of digital technology. To identify the root causes of problems, the Fishbone Diagram method was applied, while the Business Model Canvas (BMC) was used to develop business strategies. The research method includes literature review, observation, interviews, website design using WordPress, and system analysis. The findings indicate that implementing a WordPress-based e-commerce platform improves the visibility of Baduy Batik products in the digital market and expands market reach. Through the integration of Fishbone and BMC analyses, this study proposes strategic recommendations for business model development that enhance competitiveness and business sustainability.